Overcoming the Fear of Water at the Initial Stage of Learning to Swim - Obrazhey, Olga; Ображей, Ольга (Східноєвропейський національний університет ім.Лесі Українки, 2017)
The article deals with the fear of children of primary school age to open water, which appears at the initial stage of teaching swimming and is a serious obstacle to mastering the skills of swimming. Analysis of the scientific researches indicate a lack of reasonable methods of overcoming fears associated with the water during swimming training and scientific methodological developments in the prevention and overcoming fears associated with water, which leads to certain problems and violations of logical consistency in teaching swimming. The following empirical methods as questionnaires, interviews, pedagogical observations are used. The article presents the results of a study of this problem, especially: the results of the survey of primary school children who arrived at the base of the summer camp «Lastochka» in Skadovsk of Kherson region in 2016 during the month of June as well as conversations and observations with them that took place in real conditions of training swimming. This study provided the opportunity to determine the origin of fear causes of primary school age children, to reveal the reasons and statistics of accidents at open water, to identify factors fear of open water of primary school age children. The article indicates signs of the most important physical symptoms associated with the fear of open water. Methodical recommendations developed to overcome fears at the initial stage of swimming lessons in open water based on the principles of psychological impact on the minds of everyone as well as the use of innovative techniques while swimming. Methodical recommendations focus on the preparation and organization of lessons with children of primary school age, with the problem of fear of open water. They aim to overcome fear and to achieve the main goals of the swimming lessons in the summer camp to teach swimming every child. У статті розглянуто причини страху перед відкритими водоймами, які виявляються на початковому етапі навчання плавання та є серйозною перешкодою для оволодіння навичками плавання. Аналіз наукових досліджень свідчить про відсутність обґрунтованої методики подолання страхів, пов’язаних із водою, під час навчання плавання й науково-методичних розробок із попередження та подолання страхів, пов’язаних із водою, що призводить до певних труднощів і порушення логічної послідовності в навчанні плавання. У роботі використано такі емпіричні методи дослідження: анкетування, бесіди, педагогічне спостереження. У статті представлено результати дослідження з указаної проблеми, а саме: результати анкетування дітей молодшого шкільного віку, які перебували на базі літнього оздоровчого табору «Ластівка» в м. Скадовську Херсонської області у 2016 р. протягом червня-місяця. а також бесід із ними й спостережень, що відбувались у реальних умовах проведення навчальних занять із плавання. У цьому дослідженні проаналізовано причини нещасних випадків на відкритих водоймах. Визначено чинники страху відкритих водойм дітей молодшого шкільного віку. У статті зазначено прояви найбільш важливих фізичних симптомів, що пов’язані зі страхом відкритих водойм. Розроблено методичні рекомендації подолання страхів на початковому етапі занять із плавання на відкритих водоймах, які ґрунтуються на засадах психологічного впливу на свідомість кожного під час занять із плавання. У методичних рекомендаціях основнуа увагу приділено підготовці та організації занять із дітьми з проблемою страху перед відкритими водоймами. Заняття спрямовано на подолання й досягнення основної мети – навчити плавати кожну дитину.
Подолання страху відкритих водойм під час початкового навчання плавання.
Keywords: swimming; fear; primary school age; water; плавання; страх відкритих водойм; молодший шкільний вік